Influence of Socio-Demographic Factors on Academic and Career Aspirations in Secondary Schools of Kathmandu Valley (Punyawati Journal, 2026)
This study investigates how socio-demographic factors shape career development among secondary school students in Nepal's Kathmandu Valley. Using a quantitative cross-sectional approach, the research surveyed 450 students from Texas International College (Kathmandu), Tripadma Secondary School (Lalitpur), and Bageshwori Secondary School (Bhaktapur), selected through stratified random sampling. Data analysis employed statistical methods including frequency distributions, cross-tabulations, and chi-square tests to examine relationships between demographic characteristics and career aspirations. The findings reveal pronounced geographic disparities, with 72% of respondents coming from Bagmati Pradesh, indicating significant regional inequalities in educational access. Students demonstrate a dual motivational pattern, combining immediate job-seeking behavior (54.7% actively seeking employment) with sustained academic effort (36.7% achieving B+ grades), reflecting the tension between economic pressures and educational goals. Furthermore, economic background substantially influences career choices, as evidenced by 33.6% of students from agriculture dependent households prioritizing financial security over personal aspiration. While the education system maintains standardized pathways, it lacks adequate personalized career guidance, resulting in difficult school-to-work transitions. The study concludes that effective career development in Nepal necessitates comprehensive strategies that address both structural barriers and individual needs. Recommendations include implementing targeted regional development programs alongside enhanced career counseling services to better align student aspirations with practical career opportunities and foster more equitable educational outcomes across diverse socio-economic backgrounds.